PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT EKK EAGLE INDUSTRY INDONESIA - Wiwin Nur Afifah; Fathorrahman (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of the work environment and work discipline on employee performance at PT. EKK Eagle Industry Indonesia.. The research method used is a quantitative method. The sampling technique used saturated sampling and the sample obtained in this study was 69 respondents. This research uses SPSS version 26. Data analysis and testing techniques include simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, autocorrelation test, t test and F test. Based on research results, the physical work environment has a positive and significant effect on employee performance with the regression equation Y = 32.467 + 0.175X1. The hypothesis test was obtained (tcount 3.001 > ttable 1.996) and significance value (0.000 <0.05). Research results Work discipline has a positive and significant effect on employee performance with the regression equation Y = 3.831 + 0.911X2. The hypothesis test was obtained (tcount 9.175 > ttable 1.996) and significance value (0.000 <0.05). Work Environment and Work Discipline simultaneously have a positive and significant effect on employee performance with the regression equation Y = 2.962 +0.162X1 + 0.889X2. The hypothesis test was obtained (Fcount 63.143 > Ftable 3.19) and significance value (0.000 <0.05).